Fleeting Fixes, Fractured Systems: Confronting the Continuing Crisis of the Public Health Workforce - Castrucci, Brian C. (American journal of public health (1971), 2025)
According to the Staffing Up report by the de Beaumont Foundation and the Public Health National Center for Innovations, the local public health workforce must expand by 80% to ensure the delivery of foundational public health services to all communities." In COVID-19's aftermath, few could have anticipated the scale and ferocity of the political backlash against public health: sweeping legislative rollbacks of public health authority, sustained harassment of health officials, and-perhaps most consequentially-the Trump administration's proposal to cut more than $12 billion from the budgets of the CDC and the Health Resources and Services Administration.4 These proposed reductions, now the subject of ongoing legal challenges, threaten to dismantle the very infrastructure the pandemic exposed as dangerously fragile. According to the Public Health Workforce Interests and Needs Survey (PH WINS), 44% of state and local public health employees reported symptoms consistent with posttraumatic stress disorder during the COVID-19 response.5 The pandemic pushed health departments to their operational and emotional limits. Across decades of scholarship and policy analysis, the calls have remained consistent: sustained and flexible funding,8 modernization of data systems,9 and strategic investments in workforce development, including loan repayment programs.10 These priorities are neither new nor contested.